Spatial analysis of violent crimes in Metro Manila, Philippines - Mojica, Vio Jianu (Animo Repository, 2019)
Spatial patterns of murder and physical injury in Metro Manila, Philippines were visualized through conditional choropleth maps. Relationship of both crime rates with some demographic variables were investigated while accounting for possible spatial autocorrelation using spatial lag models. Results show that both crime rates tend to cluster in the northern cities of Metro Manila. Furthermore, significant spatial lag coefficients were found only for physical injury rates, with values ranging from 0.49 to 0.62, signifying a positive city-level spatial dependence of physical injury rates in Metro Manila. Moreover, some demographic covariates, such as population density, percentage of young males, education, marriage, and immigration were found to be associated with both crime rates. These results could serve as useful indicators of crime incidence; thus it is recommended that crime monitoring systems include them to aid in resource allocation and program planning for better crime prevention and security management. © 2017, © 2017 School of Criminal Justice, Michigan State University.